Effect of carboxymethylcellulose on the rheological and filtration properties of bentonite clay samples determined by experimental planning and statistical analysis - Brito,B. M. A. (2018)
Abstract Over the past few years, considerable research has been conducted using the techniques of mixture delineation and statistical modeling. Through this methodology, applications in various technological fields have been found/optimized, especially in clay technology, leading to greater efficiency and reliability. This work studied the influence of carboxymethylcellulose on the rheological and filtration properties of bentonite dispersions to be applied in water-based drilling fluids using experimental planning and statistical analysis for clay mixtures. The dispersions were prepared according to Petrobras standard EP-1EP-00011-A, which deals with the testing of water-based drilling fluid viscosifiers for oil prospecting. The clay mixtures were transformed into sodic compounds, and carboxymethylcellulose additives of high and low molar mass were added, in order to improve their rheology and filtrate volume. Experimental planning and statistical analysis were used to verify the effect. The regression models were calculated for the relation between the compositions and the following rheological properties: apparent viscosity, plastic viscosity, and filtrate volume. The significance and validity of the models were confirmed. The results showed that the 3D response surfaces of the compositions with high molecular weight carboxymethylcellulose added were the ones that most contributed to the rise in apparent viscosity and plastic viscosity, and that those with low molecular weight were the ones that most helped in the reduction of the filtrate volume. Another important observation is that the experimental planning and statistical analysis can be used as an important auxiliary tool to optimize the rheological properties and filtrate volume of bentonite clay dispersions for use in drilling fluids when carboxymethylcellulose is added.